Looking at the Link between Thinking Style and Reading Comprehension: A Case of Indonesian EFL Students at One Madrasah in Palembang, South Sumatera, Indonesia - ELSYA AGESTY (Ta'dib: Jurnal Pendidikan Islam, 2019)
This study was aimed at describing the relationship between thinking style and reading comprehension of students at one Madrasah in Palembang, South Sumatera. The method used in this study was correlational research. The population of the research was eleventh grade students. There were 452 students from eleventh grade classes as the population in this study. The sample was taken by using purposive sampling which consisted of 147 students. Furthermore, there were two variables in this research. The first one was students’ thinking style (variable X) and the second one was the students’ reading comprehension skill (variable Y). The students’ thinking style score was taken from the questionnaire, while the students’ reading comprehension score was taken from a test. Based on the data analysis, it was found that the r-obtained (-.008) was lower than r-table (0.162). Then the level of probability (p) significance (sig.2-tailed) was .928. It indicated that p (.928) was higher than 0.05. It implied that null hypothesis (H0) was accepted and the alternative hypothesis (Ha) was rejected. From the finding, it could be concluded that there was no significant relationship between the students’ thinking style and their reading comprehension skill. It showed that the students’ thinking style was not a dominant factor that affected the reading comprehension.